(untitled) (Scientific journal of the Fergana State University, 2024)
In this article "Who Knocked on the Door?" playwright Sharaf Boshbekov, who occupies a special place in Uzbek literature. The main character, who is not in the drama, and his creation are discussed. The spiritual world of the protagonist is analyzed from the point of view of writing.